Pobreza por subtração: A festa, de Ivan Ângelo - Frans Weiser (Estudos de Literatura Brasileira Contemporânea)
Roberto Schwarz highlights the exclusion of marginalized classes from discus- sions about Brazilian national identity in “Nacional por subtração” (1987). Incorporating Schwarz’s claim, as well as Engbersen’s five discourses of poverty (1999), this article first contextualizes poverty and its discussion in Brazilian liter- ary history before arguing that Ivan Ângelo’s A Festa (1976) constitutes a type of literature of poverty by subtraction. Ângelo excludes the voice of the poor from the novel, yet he does so precisely in order to call attention to the problematic manner in which literature, journalism, and bureaucratic reports claim to repre- sent the disenfranchised.